Elective Cesarean Section on Term Pregnancies Has a High Risk for Neonatal Respiratory Morbidity in Developed Countries: A Systematic Review and Meta-Analysis - Tefera, Maleda; Assefa, Nega; Mengistie, Bezatu; Abrham, Aklilu; Teji, Kedir; Worku, Teshager (Frontiers in Pediatrics, 2020)
Background: Worldwide, about 18.5 million cesarean sections are conducted annually. Of this, 21%-33% are performed in middle and high-income countries. The effectiveness of the Cesarean Section in preventing maternal and prenatal mortality and morbidity is medically justifiable. However, cesarean delivery without demanding obstetrical indications, by mere maternal request, may expose the child to several risks over benefits. Therefore, we aim to compare spontaneous vaginal delivery (vaginal delivery other than operative vaginal deliveries) and Elective Cesarean Section (Cesarean Section before the onset of labor, but not including emergency CS) in decreasing the risk of neonatal respiratory morbidity. Objective: To compare the risk of neonatal respiratory morbidity in Elective Cesarean Section and Spontaneous Vaginal Delivery. Methods: A literature search was performed through visiting an electronic database (MEDLINE, PubMed, EMBASE and CINAHL) and grey literature sources, including, Google and Google Scholar from January 2000 to May 2018. Original observational studies that reported, the risk of neonatal respiratory morbidity in relation to mode of delivery, conducted in the English language were identified and screened. Joanna Briggs Institute's quality assessment tool for observational Studies was used to critically appraise the methodological quality of studies. Synthesis of individual studies was conducted using RevMan 5.3. Heterogeneity among studies was explored using the Cochran’s Q test and the I2 statistics. Pooled effect sizes in Relative Risk Ratios with 95% confidence intervals were calculated. The flow of the study was prepared according to the Meta-analysis of Observational Studies in Epidemiology (MOOSE) checklist. Results: Sixteen studies were reviewed. A total of 327,272 neonates born by vaginal delivery and 55,246 born by Elective Cesarean Section was included in this study. The risk of neonatal respiratory morbidity was increased by 95% in neonates delivered by Elective Cesarean Section (RR=1.95; 95% CI: 1.40-2.73) as compared with neonates born by Spontaneous Vaginal Delivery. Conclusion: This study investigated the effect of mode of delivery on the respiratory morbidity without considering other risks and found that the Elective Cesarean Section has a high risk of developing neonatal respiratory morbidities when compared to Spontaneous Vaginal Delivery. So, we recommend discouraging unnecessary cesarean section. Systematic review registration: CRD42018104905.